SMES’ GROWTH STAGE MODEL: A LITERATURE REVIEW AND DEVELOPMENT MODEL - Bachtiar, Nia Kurniati; Amin, Muhammad Al (Jurnal Analisis Bisnis Ekonomi, 2019)
Growth Stage Model (GSM) is essential especially for Small and Medium Enterprises (SMEs) in order to know their position in the industry, setting their growth strategy to forecasting their future movement. The development of GSM evolves over time with a modest 4 (four) stages to the current 6 (six) stages. The measurement, variable used and indication of each model also develop. This article is a literature study article which will compare, summarize and synthesize the literatures about GSM. Finally, this article find a challenging moment created by industrial revolution 4.0 that effected business especially SMEs in their growth stage. Hence, this article provides the proposed model of modern GSM as an answer of industrial revolution 4.0 challenge to business world.